INTEGRITAS SEBAGAI PEMODERASI PENGARUH TEKANAN ANGGARAN WAKTU, KOMPLEKSITAS TUGAS, DAN PENGALAMAN KERJA PADA KUALITAS AUDIT - Susilo, Affonsus Umar Woko (E-Jurnal Ekonomi dan Bisnis Universitas Udayana, 2017)
Financial and Development Supervisory Board’s audit quality reflects the effectiveness of internal controls in providing assurance to increase governance accountability and transparency. This study aims to obtain empirical evidence of integrity as a moderating in the influence of time budget pressure, task complexity, and work experience on audit quality. This research was conducted at the Financial and Development Supervisory Board Representative Bali Province. The number of respondents (47 auditors) were selected by purposive sampling method. The analyzed data is primary data. The data is obtained using a questionnaire. Furthermore, research hypotheses were tested with Moderated Regression Analysis. Hypothesis testing results show that integrity is not a moderating variable in the influence of time budget pressure on audit quality. Integrity is not a moderating variable in the influence of task complexity on audit quality. In addition, integrity is not a moderating variable in the influence of work experience on audit quality.
Keywords: time budget pressure, task complexity, work experience, audit quality